Perbandingan Suhu pada Ruang Terbuka Hijau (RTH) dan non RTH di Area Megamas Manado - Djeli Alvi Tulandi (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2022)
This study was conducted with the aim of knowing changes in temperature in the urban forest green open space (RTH) area and in non-green open space areas in the Megamas Manado complex. This study uses a descriptive analytical design. In this study, there are microclimate variables and the determination of the sample using purposive sampling method. This study aims to test the hypothesis whether it is true that the temperature in the green open space area is lower than the temperature in the non green open space area. There are three data collection points, namely in the urban forest area, the Mega Mall area, and the Marina-2 Manado area. Based on the average temperature value, it shows that the temperature in the green open space is lower than the temperature in the non green open area. The statistical test results also state that there is a significant (significant) difference between the temperature in the green open space and the temperature in the non green open space. Therefore, this research concludes that the Green Open Space Area (RTH) can reduce solar energy, so that the temperature in the green open space area is lower than the temperature in the non-RTH area.